ESTRATÉGIAS DE POLIDEZ NA COMUNICAÇÃO AÉREA (Muitas Vozes, 2022)
Pragmatic studies are interested in demonstrating the concrete use of language in its varied contexts and the effect it has on our listeners on what we say. This work presents an approach related to pragmatics, but specifically to politeness with regard to the linguistic behavior that manages relationships in our society, based on the dialogue records taken from the Tu-154's black box. The research uses as a foundation the Theory of Politeness, drawing on studies by Brown and Levinson (1987), Goffman's concept of face (1967), Spencer-Oatey's conceptions of power and distance (2005) to demonstrate that the act speech carries a threat to the public image of those included in the chain of command that can interfere with the decisions of military aircraft pilots, that is, both speaker and listener are prone to be linguistically injured. With the analysis, it was possible to identify a succession of events for the preservation of the face that led to the accident of the aircraft. Thus, it is possible to conclude that in hierarchical relationships, among the most uncomfortable types of problems that arise in face negotiation, are issues related to the loss of status.